Efficient alkane hydroxylation catalysis of nickel(ii) complexes with oxazoline donor containing tripodal tetradentate ligands. Issue 18 (23rd April 2020) - Terao, Ikumi; Horii, Sena; Nakazawa, Jun; Okamura, Masaya; Hikichi, Shiro
Abstract : Nickel(ii ) complexes with oxazoline-based tripodal ligands are efficient catalysts for alkane oxidation, and reaction rates and oxidizing position selectivity are controlled by the structural properties of the substituent groups on the ligands. Abstract : Tris(oxazolynylmethyl)amine TOA R (where R denotes the substituent groups on the fourth position of the oxazoline rings) complexes of nickel(ii ) have been synthesized as catalyst precursors for alkane oxidation with meta -chloroperoxybenzoic acid ( m -CPBA). The molecular structures of acetato, nitrato, meta -chlorobenzoato and chlorido complexes with TOA Me2 have been determined using X-ray crystallography. The bulkiness of the substituent groups R affects the coordination environment of the nickel(ii ) centers, as has been demonstrated by comparison of the molecular structures of chlorido complexes with TOA Me2 and TOA t Bu . The nickel(ii )-acetato complex with TOA Me2 is an efficient catalyst precursor compared with the tris(pyridylmethyl)amine (TPA) analogue. Oxazolynyl donors' strong σ-electron donating ability will enhance the catalytic activity. Catalytic reaction rates and substrate oxidizing position selectivity are controlled by the structural properties of the R of TOA R . Reaction of the acetato complex with TOA Me2 and m -CPBA yields the corresponding acylperoxido species, which can be detected using spectroscopy. Kinetic studies of the decay process of the acylperoxido species suggest that the acylperoxido species is a precursor of an active species for alkane oxidation.